Planetary Boundaries Nurturing the Grand Narrative of the Right to a Healthy Environment? - Lähteenmäki-Uutela, Anu; Ituarte-Lima, Claudia; Turunen, Topi; Ott, Anna; Lonkila, Annika; Haukioja, Teemu (IOS Press, 2026)
The profound changes in Earth systems dynamics are affecting the health of the entire planet and the realization of a broad range of human rights. In this paper, we propose that the grand narrative of human rights including the legal right to a clean, healthy and sustainable environment recognized by the United Nations in 2022 requires the acknowledgment of the interconnected challenges posed by planetary crises. We discuss how planetary boundaries (PB) research can provide evidence-based arguments and clarify State duties concerning their international human rights law commitments. The economic, social and cultural rights are deeply connected with the right to a healthy environment. Human rights to water, food, or health, for example, can all be understood in the context of Earth systems change. Civil and political rights go beyond individuals to include also collective action and participation to tackle planetary social-ecological challenges. Gaps remain in human rights law concerning some of the PBs, which risks overlooking the interconnected drivers of ecosystem degradation. Clearer legal standing and justification for legal demands, for example concerning the impacts of water use, land use and deforestation, are needed to tackle PB overshoot. States must act at various spaces including the global economic systems and the global supply chains of goods and services for humanity to reach planetary safe and just spaces. Weaving international human rights law and advances at various geographical scales on the right to a healthy environment with PB provides a powerful tool for defending the prerequisites of good life for everyone, everywhere.